90 Days toxicological assessment of hydroethanolic leaf extract of Ipomoea asarifolia (Desr.) Roem. and Schult. (Convolvulaceae) in rats. (4th November 2015) - Akindele, Abidemi J.; Unachukwu, Emeka G.; Osiagwu, Daniel D.
Abstract: Ethnopharmacological relevance: Ipomoea asarifolia (Convolvulacae), commonly known as "morning glory" is found across West Africa. Preparations of the plant are used traditionally for the treatment of diverse ailments including diabetes, neuralgia, arthritic pain and stomach ache. This study was designed to assess the safety profile of the hydroethanolic leaf extract of I. asarifolia through a 90-day subchronic toxicity study in rats. Materials and methods: I. asarifolia was administered p.o. at doses of 40, 200 and 1000 mg/kg to separate groups of rats for 90 days. Distilled water was given p.o. to rats in the control group. Some set of rats in each group were left for additional 30 days without administration of the extract for reversibility study. Animals were weighed weekly and relevant parameters were assayed at the end of the main and reversibility study periods. Results: There was no significant change ( p >0.05) in the body weight of rats, and food and water intake in I. asarifolia treated groups compared with control. I. asarifolia (40–1000 mg/kg) significantly but reversibly reduced ( p <0.05, 0.001) sperm motility and count. The extract did not generally cause significant change ( p >0.05) in the weight of vital organs and haematological parameters except in the case of reversible reduction in the level of haemoglobin and red blood cell count ( p <0.01; 40 mg/kg). The level of biochemical parameters and electrolytes were not significantly changed ( p >0.05) except for the reversible reduction in the level of aspartate aminotransferase (AST; p <0.0001; 200 and 1000 mg/kg) and increase in the level of Na + ( p <0.01; 200 mg/kg). The level of kidney reduced glutathione (GSH) was reversibly increased ( p <0.01; 1000 mg/kg) while the level of enzymatic and non-enzymatic in vivo antioxidants was generally comparable and not significantly different ( p >0.05) from control in respect of all other vital organs. Histological presentations were generally normal in respect of the liver, kidneys, brain, heart, lungs, pancreas, spleen and testes. Conclusions: The findings in this study suggest that the hydroethanolic leaf extract of I. asarifolia is relatively safe administered orally for an extended period with potential renal in vivo antioxidant activities. However, the extract may cause reversible male sterility, anaemia and hypernatraemia. Graphical abstract: